Chitosan-Ag-TiO2 films: An effective photocatalyst under visible light. (1st November 2018) - Jbeli, A.; Hamden, Z.; Bouattour, S.; Ferraria, A.M.; Conceição, D.S.; Ferreira, L.F. Vieira; Chehimi, M.M.; do Rego, A.M. Botelho; Rei Vilar, M.; Boufi, S.
Graphical abstract: Highlights: Chitosan thin films: suitable supports for immobilizing Ag/TiO2 nanostructures. Besides Ag NPs, also AgCl is formed after the hydrothermal treatment at 100 °C. Chitosan-AgCl/Ag/TiO2 degrades/mineralizes organic compounds under Vis light. TiO2 /Ag hybrid does not spread in the catalyzed medium due to the substrate. Abstract: Aiming the degradation of harmful molecules under visible light, new photocatalytic systems were created. For this purpose, the surface of chitosan thin films was modified in heterogeneous phase via a simple and straightforward mild chemical process: chemisorption of silver ions followed by the synthesis in situ of TiO2 at low temperature (100 °C). A high photocatalytic activity under visible light was observed, leading to the degradation and/or mineralization of different organic products such as o-toluidine, salicylic acid and 4-aminomethyl benzoic acid. This efficiency is partly attributed to the formation of Ag NPs and also to the unexpected appearance of AgCl NPs, likely formed from the residual chlorine contained in the chitosan. The resulting TiO2 /Ag/AgCl/Chitosan system is easy to prepare under mild conditions, avoiding calcination treatments and opens new perspectives for the production of visible light-driven photocatalysts. Samples were analysed by different techniques: XRD, Raman, FE-SEM, XPS, TGA, GSDR, LIF and LIP.